Subtle Changes in Medication-taking Are Associated With Incident Mild Cognitive Impairment. (July 2021) - Dorociak, Katherine E.; Mattek, Nora; Ferguson, John E.; Beattie, Zachary T.; Sharma, Nicole; Kaye, Jeffrey A.; Leese, Mira I.; Doane, Bridget M.; Hughes, Adriana M.
Abstract : Introduction: Medication-taking is a routine instrumental activity of daily living affected by mild cognitive impairment (MCI) but difficult to measure with clinical tools. This prospective longitudinal study examined in-home medication-taking and transition from normative aging to MCI. Methods: Daily, weekly, and monthly medication-taking metrics derived from an instrumented pillbox were examined in 64 healthy cognitively intact older adults (Mage =85.5 y) followed for a mean of 2.3 years; 9 transitioned to MCI during study follow-up. Results: In the time up to and after MCI diagnosis, incident MCI participants opened their pillbox later in the day (by 19 min/mo; β=0.46, P<0.001) and had increased day-to-day variability in the first pillbox opening over time (by 4 min/mo) as compared with stable cognitively intact participants (β=4.0, P=0.003). Discussion: Individuals who transitioned to MCI opened their pillboxes later in the day and were more variable in their medication-taking habits. These differences increased in the time up to and after diagnosis of MCI. Unobtrusive medication-taking monitoring is an ecologically valid approach for identifying early activity of daily living changes that signal transition to MCI.